2020
DOI: 10.1101/2020.11.04.367987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A combined flow injection/reversed phase chromatography – high resolution mass spectrometry workflow for accurate absolute lipid quantification with13C- internal standards

Abstract: We propose a fully automated novel workflow for lipidomics based on flow injection- followed by liquid chromatography high resolution mass spectrometry (FI/LC-HRMS). The workflow combined in-depth characterization of the lipidome achieved via reversed phase LC-HRMS with absolute quantification as obtained by a high number of lipid species-specific- and/or retention time (RT) matched/class-specific calibrants. The lipidome of 13C labelled yeast (LILY) provided a cost efficient, large panel of internal standards… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(114 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, the cells were successfully differentiated towards the chondrogenic, adipogenic, and osteogenic lineage. This study's findings are in accordance with observed ganglioside regulations of our previous study on MSC and adipogenic cell differentiation coming from a different stem cell donor source (female, other adipose tissue part) (Schoeny et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the cells were successfully differentiated towards the chondrogenic, adipogenic, and osteogenic lineage. This study's findings are in accordance with observed ganglioside regulations of our previous study on MSC and adipogenic cell differentiation coming from a different stem cell donor source (female, other adipose tissue part) (Schoeny et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“… 89 Here, we want to emphasize the possibility of class or retention-time specific standardization if the target metabolite or lipid is not present in the yeast extract. By using these labeled compounds as class or retention-time specific ISTD if the target analyte is not present in the yeast extract, 90 the list of possible analytes in a quantitative approach can further be enlarged and adapted to the sample of interest.…”
Section: Stable Isotope Labelingmentioning
confidence: 99%
“…In metabolomics studies using high-resolution mass spectrometry (MS), a precise mass-tocharge ratio (m/z) value is measured to deduce the compositional formulae of a metabolite-derived ion 1) . In addition, the product ion spectrum of the detected ion is simultaneously acquired using the data-dependent acquisition (DDA) mode of various tandem MS, such as quadrupole-time-of-flight (Q-TOF) MS [2][3][4][5][6][7] . The fragmentation pattern in the product ion spectrum is also used to annotate structural information regarding the metabolite.…”
Section: Introductionmentioning
confidence: 99%